Self‐assembling polymeric dendritic peptide as functional osteogenic matrix for periodontal regeneration scaffolds—an in vitro study. (20th March 2019) - Das, Eva C.; Dhawan, Sameer; Babu, Jisha; Anil Kumar, PR; Kumary, Thrikkovil Variathu; Haridas, V; Komath, Manoj
Abstract : Objective: Regeneration of periodontal defects is challenging as it necessitates the formation of complex tissue structure with cementum, periodontal ligament, and alveolar bone. Rather than the conventional barrier membranes, scaffolds mimicking extracellular matrix (ECM) can achieve faster healing as they promote migration, adhesion, and differentiation of native progenitor cells. This work explores the possibility of a functional osteogenic matrix based on self‐assembling peptide appended dendritic polydiacetylene in regenerating diseased periodontia. Method: The amino acid lysine was appended onto a diacetylene core, which was converted to a polymeric dendritic lysine matrix (Lys‐ PDA ) through photopolymerization. This bioactive matrix was evaluated in vitro for the viability, adhesion, spreading, and differentiation of cultured human periodontal ligament (hPDL) progenitor cells. Its osteogenic differentiation was analysed by histologic staining and expression of osteogenic markers (alkaline phosphatase and Osteonectin). Electrospun polycaprolactone (PCL) mat, a candidate barrier material, was fabricated and functionalized with Lys‐PDA matrix, and the cell viability, adhesion, and spreading of hPDL cells were evaluated. Results: The dendritic Lys‐PDA matrix well supported the hPDL cell growth and differentiation. The cells were viable and showed good cytoskeletal organization. Early expression of osteogenic markers and mineralization was noted in vitro in the presence of Lys‐PDA matrix. The electrospun PCL mat functionalized with Lys‐PDA maintained the viability, morphology, and spreading of the hPDL cells. Significance: The ECM mimetic dendritic peptide matrices are capable of hosting and differentiating cells which can lead to the regeneration of periodontal tissue architecture. They could be used in conjunction with barrier membranes for better results.